Dominant regulation of long‐term allograft survival is mediated by microRNA‐142. Issue 10 (23rd April 2020) - Anandagoda, Nelomi; Roberts, Luke B.; Willis, Joanna C. D.; Sarathchandra, Padmini; Xiao, Fang; Jackson, Ian; Hertweck, Arnulf; Kapoor, Puja; Jenner, Richard G.; Howard, Jane K.; Lord, Graham M.
Abstract : Organ transplantation is often lifesaving, but the long‐term deleterious effects of combinatorial immunosuppression regimens and allograft failure cause significant morbidity and mortality. Long‐term graft survival in the absence of continuing immunosuppression, defined as operational tolerance, has never been described in the context of multiple major histocompatibility complex (MHC) mismatches. Here, we show that miR‐142 deficiency leads to indefinite allograft survival in a fully MHC mismatched murine cardiac transplant model in the absence of exogenous immunosuppression. We demonstrate that the cause of indefinite allograft survival in the absence of miR‐142 maps specifically to the T cell compartment. Of therapeutic relevance, temporal deletion of miR‐142 in adult mice prior to transplantation of a fully MHC mismatched skin allograft resulted in prolonged allograft survival. Mechanistically, miR‐142 directly targets Tgfbr1 for repression in regulatory T cells (TREG ). This leads to increased TREG sensitivity to transforming growth factor – beta and promotes transplant tolerance via an augmented peripheral TREG response in the absence of miR‐142. These data identify manipulation of miR‐142 as a promising approach for the induction of tolerance in human transplantation. Abstract : Using mouse models of fully MHC‐mismatched organ transplantation, the authors show that deletion of microRNA‐142 in T cells results in long‐term allograft survival by inhibiting T cell–mediated allograft rejection via dominant tolerance.